Integrasi Teknologi dalam Pembelajaran Pendidikan Agama Kristen (PAK) sebagai Peluang dan Tantangan di Era Digital - Apriyanti R. S; Djoys Anneke Rantung; Lamhot Naibaho (Journal on Education, 2023)
In the digital era that continues to develop, the integration of technology into the study of Christian religious education is a hot and important topic. The purpose of this article is to explore the opportunities and challenges of integrating technology into Christian religious education in the digital age. We look at how technology can provide new opportunities for interactive delivery of Christian religious material, increase student engagement and broaden the scope of learning. In this article, we highlight the benefits of integrating technology into Christian religious education, including the use of multimedia, e-learning platforms, applications mobile and social media. We will also discuss the importance of teacher training and development for the effective use of technology and the support and cooperation role of parents, church, and society. In addressing this, we propose an approach that focuses on developing digital literacy, responsible use of technology, understanding its ethical implications, and maintaining close human relationships between teachers and students. Through this research, we conclude that integrating technology into Christian religious education classrooms can provide significant opportunities to enhance students' learning experiences and broaden access to Christian religious education materials.